Multimedia Related Vocabulary Learning Strategies among English as a Foreign Language Algerian Students - Adela Talbi spouse Hassani (The Journal of Studies in Language, Culture and Society, 2024)
The focus in the present paper is on the evolution of students' behaviour in terms of Vocabulary Learning Strategies use from Year 1 to Year 3, with special focus on the type of strategies that might be conductive to larger vocabulary size.  The study is undertaken with 184 EFL undergraduate students at the University of Algiers 2, and the data collection instruments comprise: the Vocabulary Size Test (VST) (Nation 2007), VLS Questionnaire (Schmitt 1997) and a general vocabulary learning open questionnaire. Findings reveal that the whole population has similar preferences for Determination and Metacognitive Strategies, while Social Strategies are the least frequently used. Besides, analysis of correlations between variables does not demonstrate any significant impact of VLS use on vocabulary size growth, except for the low-intermediate freshers for whom Metacognitive Strategies involving the use of the Internet to search for information or to communicate seem to be significantly correlated to their vocabulary size. These findings have interesting implications for the classroom as they stress the importance of integrating explicit vocabulary instruction as well as strategy training to reinforce the students’ vocabulary knowledge and build up stronger learners’ autonomy, and it shows the potential support of multimedia related strategies in developing this knowledge.